Vesper flights eaudiobook - Macdonald, Helen (Recorded Books Inc., 2020)
Animals don't exist in order to teach us things, but that is what they have always done, and most of what they teach us is what we think we know about ourselves. From the bestselling author of H is for Hawk comes Vesper Flights, a transcendent collection of essays about the human relationship to the natural world. Helen Macdonald brings together a collection of her best-loved writing along with new pieces covering a thrilling range of subjects. There are essays here on headaches, on catching swans, on hunting mushrooms, on twentiethcentury spies, on numinous experiences and high-rise buildings; on nests and wild pigs and the tribulations of farming ostriches. Vesper Flights is a book about observation, fascination, time, memory, love and loss and how we make the world around us. Moving and frank, personal and political, it confirms Helen Macdonald as one of this century's greatest nature writers.